Heme enables proper positioning of Drosha and DGCR8 on primary microRNAs. Issue 1 (December 2017) - Partin, Alexander; Ngo, Tri; Herrell, Emily; Jeong, Byung-Cheon; Hon, Gary; Nam, Yunsun
Abstract MicroRNAs regulate the expression of many proteins and require specific maturation steps. Primary microRNA transcripts (pri-miRs) are cleaved by Microprocessor, a complex containing the RNase Drosha and its partner protein, DGCR8. Although DGCR8 is known to bind heme, the molecular role of heme in pri-miR processing is unknown. Here we show that heme is critical for Microprocessor to process pri-miRs with high fidelity. Furthermore, the degree of inherent heme dependence varies for different pri-miRs. Heme-dependent pri-miRs fail to properly recruit Drosha, but heme-bound DGCR8 can correct erroneous binding events. Rather than changing the oligomerization state, heme induces a conformational change in DGCR8. Finally, we demonstrate that heme activates DGCR8 to recognize pri-miRs by specifically binding the terminal loop near the 3′ single-stranded segment. Drosha and DGCR8 constitute the core Microprocessor complex, which processes primary microRNAs (pri-miRs) into mature microRNAs. Here the authors show that heme is essential for the proper processing of pri-miRs by Drosha-DGCR8, and the molecular mechanism by which heme enhances processing fidelity.